University of Malaya dental students' attitudes towards communication skills learning: Implications for dental education - Nor, N.A.M.; Yusof, Z.Y.M.; Shahidan, M.N.F.M. (2010)
The Ministry of Higher Education in Malaysia has called for the implementation of a soft skills module in all public universities in Malaysia. In response to this and as part of curriculum development efforts for a new integrated program for 2011, a study was undertaken to improve the University of Malaya (UM) Faculty of Dentistry's communication skills course. One of the study objectives was to investigate dental students' attitudes towards communication skills learning and the association between their attitudes and demographic and education-related characteristics. A cross-sectional survey-using a self-administered twenty-four-item adapted Communication Skills Attitude Scale (CSAS) that contained both positive (PAS) and negative (NAS) attitude subscales-was carried out targeting all final-year dental students at the UM and the Universiti Kebangsaan Malaysia (UKM). A total of 148 students completed the survey, yielding a response rate of 88.1 percent. Overall, UKM students had significantly more positive attitudes towards communication skills learning (PAS score: mean=48.69, SD=4.48, p<0.001) than UM students (mean=46.03, SD=4.22). There was no statistically significant difference in negative attitudes between the two groups. UKM students with more positive attitudes tended to be female (p<0.05). UM students with more negative attitudes perceived themselves as poor communicators (p<0.05), and UKM students with more negative attitudes tended to have poor English proficiency (p<0.05). This study found that both UM and UKM final-year dental students have positive and negative attitudes towards learning communication skills. These attitudes were significantly associated with certain background and education-related attributes. Outcomes of this study served as a valuable guide in strengthening the communication skills course for the UM's new, integrated dental curriculum.